PENGEMBANGAN LKPD BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN BIOLOGI KELAS XI SMA - Pertiwi, Rani; Yeni J, Fetri; Rayendra; Masnur, Alkadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students in Biology learning, particularly on the skeletal system topic, due to the use of conventional worksheets that were unable to visualize abstract concepts effectively. In addition, students often experienced difficulties in understanding the structure and functions of the human skeletal system and showed low engagement during the learning process. Therefore, this study aimed to develop an Augmented Reality (AR)-based Student Worksheet (LKPD) for Grade XI Senior High School Biology and to determine its validity, practicality, and effectiveness. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included material experts, media experts, Biology teachers, and 36 Grade XI students at SMA Negeri 1 Solok Selatan. Data were collected through validation sheets, practicality questionnaires, and learning outcome tests. The results indicated that the developed AR-based LKPD achieved a material validity score of 96.67% and media validity scores of 95.38% and 93.85%, all categorized as very valid. The practicality test yielded an average score of 93.01%, indicating that the product was very practical and easy to use. Furthermore, the effectiveness test showed a significant improvement in students’ learning outcomes, with an NGain score of 97.67%, categorized as highly effective. Based on these findings, the AR-based LKPD was proven to be valid, practical, and effective for supporting Biology learning on the human skeletal system in Grade XI Senior High School.